PENERAPAN TEKNOLOGI LUBANG RESAPAN BIOPORI SEBAGAI UPAYA PENINGKATAN KESADARAN LINGKUNGAN PADA MASYARAKAT - Syariva, Ifta Nur; Mirzaq, Nilatul; Putri, Ihda Makarima; Amanda, Chaerunisa Syifa; Muasomah (CV. Kalimasada Group, 2025)
This study aims to enhance community understanding of organic waste management and rainwater utilization through biopore infiltration holes (LRB). A descriptive qualitative method was applied, using primary data from observations, interviews, and documentation, and secondary data from literature. Activities included material preparation, socialization, construction practice, and evaluation. Results showed residents’ enthusiasm, improved knowledge, and commitment to applying LRB at home. LRB can reduce organic waste volume, improve soil infiltration, prevent waterlogging, and produce compost, making it an effective, simple, low-cost, and eco-friendly technology for household-level waste management.